ANALISIS FAKTOR TERBENTUKNYA KUALITAS KEHIDUPAN KAMPUS (QUALITY OF COLLEGE LIFE - MRR Tiyas Maheni DK (Admisi dan Bisnis, 2016)
The process of building Quality of CollegeLife to achieve maximum goals should bebuilt with the proper instruments. Becausethe instrument as a foundation thatsustains the activity of building a campusin College Quality of Life. Another virtueof this research, the formulation of themodel is the Quality of College Life courseat the college. Cover models in this studycan provide a positive contribution to themanagement of study programs in an effortto realize Quality of College Life. Object ofthis study was student. Variables to bemeasured and tested in this study issatisfaction with faculty, satisfaction withfacilities Prodi, and the quality of campuslife and student goal orientation andbehavior. Accidental sampling method is asampling technique, while for analyticaltechniques that are used confirmatoryfactor analysis and Regression Weight, onthe SEM using AMOS 18.0 computerizedpackage. Other results from this study inaddition to strengthening the theory, andmanagerial policy for the college). Thisscientific articles, is expected to be areference to the theoretical research ofQuality of College Life in the future.